Financial system architecture and technological vulnerability - Selman Erol; Michael Junho Lee (Federal Reserve Bank of New York, 2024)
This paper presents a framework to study the technological resiliency of financial system architecture. Financial market infrastructures, or platforms, compete with services that play critical functions along various stages in the lifecycle of a trade, and make investments in technological resiliency to guard against attackers seeking to exploit system weaknesses. Platforms' financial network effects attenuate competition between platforms on security. Exposure to vulnerabilities is magnified in the presence of strategic adversaries. Private provision of technological resiliency is generally sub-optimal, with overand under-investment in security depending on market structure. Vulnerabilities evolve over the maturity of a financial system, but there generically exists a tipping point at which technological resiliency diverges from optimal and creates technological drag on the financial system. We find supportive evidence in tri-party repo settlement: the exit of duopolist resulted in a significant drop in IT-related investment by the sole provider, even as peer firms ramp up investment.
Additional information: Revised October 2024
Keywords: D82; D86; D47; G29; 330; financial market architecture; technological vulnerability; cyber risk; financial stability